Safety and Tolerability of Antipsychotic Drugs in Pediatric Patients: Data From a 1-Year Naturalistic Study - Cicala, Giuseppe; Barbieri, Maria A.; Santoro, Vincenza; Tata, Carmela; Colucci, Pia V.; Vanadia, Francesca; Drago, Flavia; Russo, Carmelita; Cutroneo, Paola M.; Gagliano, Antonella; Spina, Edoardo; Germanò, Eva (Frontiers in Psychiatry, 2020)
Background: Antipsychotic drugs (APs) are increasingly used to treat a variety of psychiatric disorders in children and adolescents. However, their safety and tolerability profiles, when used in a developmental age context show different characteristics from the ones observed in adult patients. Treatment with APs in paediatric patients is often long-term. However, the tolerability data regarding these patients mostly derive from short-term studies. Methods: Starting from April 2017, for a one-year period, patients between 4 and 18 years of age followed by five units of developmental age neuropsychiatry, who initiated a treatment with at least an antipsychotic drug (ATC class N05A) were included into the study. Patients related data have been collected at baseline and regularly thereafter, as allowed by the clinical routine. Changes to continuous variables over time have been analysed using a linear mixed model in subsamples of our population treated with risperidone or aripiprazole. Results: During the observation period, 158 patients were initially enrolled but only 116 completed 12 months of therapy with an AP. Risperidone was the most used AP (n=52) followed by aripiprazole (n=44) and olanzapine (n=7). For both the aripiprazole and risperidone groups, the mean BMI (P < 0.001 for both groups), heart rate (P = 0.026 for aripiprazole group and P < 0.001 for the risperidone one) values significantly increased over time. The mean prolactin concentration value significantly increased over time only in the risperidone group (P = 0.04). Eighty-six patients experienced at least one ADR accounting for a total of 238 specific reactions with the most frequent being weight gain (n=34), increased serum prolactin levels (n=21), hyperphagia (n=20), and hypercholesterolemia (n=14). Among these, only 24 ADR were classifiable as serious. Conclusions: The results of this study confirm that risperidone and aripiprazole are relatively well-tolerated therapeutic options for the treatment of a variety of psychiatric disorders in paediatric patients. However, findings such as statistically significant the increments of BMI and heart rate mean values, the variations over time in prolactin levels observed with risperidone and the differences between the two drugs remark the necessity of systematic monitoring.